2016
DOI: 10.18520/cs/v111/i5/913-919
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Source Parameters of the 25 April 2015, M<sub>w</sub> = 7.8 Gorkha, Nepal Earthquake from Synthetic Aperture Radar Interferometry

Abstract: mountain range, NW India, and its hinterland: the U-Pb and Hf isotope record of detrital zircon. Precambrian Res., 2011, 187, 155-164. 27

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The mid-crustal ramp structure is known to have accumulating stress in the inter-seismic period as suggested by micro-seismic and geodetic observations (Pandey et al, 1995;Avouac, 2003). Keeping these observations in view, Sreejith et al, 2016a have suggested that the Gorkha earthquake was possibly caused by the release of inter-seismic strain energy accumulated in the environs of mid-crustal ramp due to plate boundary forces. However, it appears that the hypothesis put forward in this study need to be verified using more sophisticated models.…”
Section: W 78 Gorkha Nepal Earthquakementioning
confidence: 96%
See 1 more Smart Citation
“…The mid-crustal ramp structure is known to have accumulating stress in the inter-seismic period as suggested by micro-seismic and geodetic observations (Pandey et al, 1995;Avouac, 2003). Keeping these observations in view, Sreejith et al, 2016a have suggested that the Gorkha earthquake was possibly caused by the release of inter-seismic strain energy accumulated in the environs of mid-crustal ramp due to plate boundary forces. However, it appears that the hypothesis put forward in this study need to be verified using more sophisticated models.…”
Section: W 78 Gorkha Nepal Earthquakementioning
confidence: 96%
“…The observed deformation pattern of the coseismic deformation was explained by a simple forward model (Sreejith, et al, 2016a) consisting of planar dislocation buried in elastic half-space (Okada, 1985). The model revealed that the overall rupture occurred on a 170 km long, 60 km wide fault along the strike (286°) and dipping north (dip=15°) with large amount of slip (4.5 m) confined to the center (95×22 km2) and less slip (0.25 m) on the surrounding part of the fault plane (Fig.…”
Section: W 78 Gorkha Nepal Earthquakementioning
confidence: 99%